Feedback control of collective dynamics in an oscillator population with time-dependent connectivity - Rosenblum, Michael (Frontiers in Network Physiology, 2024)
We present a numerical study of pulsatile feedback-based control of synchrony level in a highlyinterconnected oscillatory network. We focus on a nontrivial case when the system is close to the synchronization transition point and exhibits collective rhythm with strong amplitude modulation.We pay special attention to technical but essential steps like causal real-time extraction of the signal of interest from a noisy measurement and estimation of instantaneous phase and amplitude.The feedback loop's parameters are tuned automatically to suppress synchrony. Though the study is motivated by neuroscience, the results are relevant to controlling oscillatory activity in ensembles of various natures and, thus, to the rapidly developing field of network physiology.